Integrating Akidah Akhlak Values through the ALAMKU 3R Program in Madrasah Ibtidaiyah - Jifa Hilda Aulia AlMujib; Wachyudi Achmad (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
Environmental education in primary schools is often implemented through technical activities without being systematically integrated into students’ moral and theological development. In Islamic primary education, Akidah Akhlak instruction also tends to focus on doctrinal understanding rather than contextual ecological behavior, resulting in a gap between religious values and students’ environmental responsibility. This study aims to examine the integration of values into ecological education through the ALAMKU (Reduce, Reuse, Recycle) program at MI Ma’arif Pagerwojo. This research employed a qualitative case study approach conducted over three months. Data were collected through semi-structured interviews, observations, and document analysis involving the headmaster, teachers, and 24 students. Data were analyzed using an interactive qualitative analysis model through data condensation, data display, and conclusion drawing. The findings reveal that the integration operated through curriculum-based theological alignment, structured 3R ecological practices, and cultural reinforcement through school habituation. The theological principles of tawhid, amanah, and khalifah functioned as moral drivers of students’ ecological behavior. The program also contributed to an approximately 80% reduction in weekly plastic waste and improved students’ environmental responsibility and discipline. In conclusion, the integration of Akidah Akhlak values through the ALAMKU 3R program demonstrates that faith-based ecological education can effectively strengthen students’ ecological character and generate measurable sustainability outcomes in Islamic primary education.